Evolutionary problems in centrosome and centriole biology. (12th May 2015) - Ross, L.; Normark, B. B.
Abstract Centrosomes have been an enigma to evolutionary biologists. Either they have been the subject of ill‐founded speculation or they have been ignored. Here, we highlight evolutionary paradoxes and problems of centrosome and centriole evolution and seek to understand them in the light of recent advances in centrosome biology. Most evolutionary accounts of centrosome evolution have been based on the hypothesis that centrosomes are replicators, independent of the nucleus and cytoplasm. It is now clear, however, that this hypothesis is not tenable. Instead, centrosomes are formed de novo each cell division, with the presence of an old centrosome regulating, but not essential for, the assembly of a new one. Centrosomes are the microtubule‐organizing centres of cells. They can potentially affect sensory and motor characters (as the basal body of cilia), as well as the movements of chromosomes during cell division. This latter role does not seem essential, however, except in male meiosis, and the reasons for this remain unclear. Although the centrosome is absent in some taxa, when it is present, its structure is extraordinarily conserved: in most taxa across eukaryotes, it does not appear to evolve at all. And yet a few insect groups display spectacular hypertrophy of the centrioles. We discuss how this might relate to the unusual reproductive system found in these insects. Finally, we discuss why the fate of centrosomes in sperm and early embryos might differ between different groups of animals.